An evaluation of the hospital component of general practice vocational training. - Kearley, K (1990)
The contribution of the hospital component of vocational training to the needs of the future general practitioner was investigated by undertaking semi-structured interviews with a representative sample of doctors involved. The findings indicated that, in general, training was failing to address objectives perceived to be important for general practice by the study sample. Problems related to the context and style of hospital training also emerged, which appeared to be limiting the learning potential of this type of experience for general practitioner trainees. It is apparent that there is a need to clarify priority objectives for the hospital component of vocational training, and ensure that it provides the opportunity to achieve them.